2019
DOI: 10.17233/sosyoekonomi.2019.02.07
|View full text |Cite
|
Sign up to set email alerts
|

External Debt and Economic Growth in Turkey: An Empirical Analysis

Abstract: This study analyzes the impact of external debt stock, openness and the consumer price index on economic growth, based on time series data obtained from the World Bank for the period from 1970 to 2016. For this report's purpose, the stability of the series was analyzed. Having identified the series to have first degree l(1) stability, the ARDL bounds testing approach was applied and a relationship of cointegration was established. In light of these findings, it has been observed that external debt has a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…Thus, a decrease in debt stock could shrink expansion opportunities and lead to a long-run decrease in GDP growth. Similar findings have been documented by previous authors [12,13]. Moreover, [10] also showed how debt stock initially derails economic growth, but improve it subsequently.…”
Section: Discussion Of Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, a decrease in debt stock could shrink expansion opportunities and lead to a long-run decrease in GDP growth. Similar findings have been documented by previous authors [12,13]. Moreover, [10] also showed how debt stock initially derails economic growth, but improve it subsequently.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…The issue of how debt influences economic growth has been a subject of interest in the empirical literature over the years. In much of the extant studies, the approaches adopted have been typically linear, based on the assumption that the debt -growth nexus is monotonic [9,10,11,12,13]. As a result, findings of these IOP Publishing doi:10.1088/1755-1315/1054/1/012053 3 studies have been inconsistent, for both the short-run and the long-run.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other empirical literature supports a positive association between external debt and growth (Gövdeli, 2019;Musibau et al, 2018). Nonetheless, other previous studies showed no significant relationship between external debt and economic growth (Hassan et al, 2015;Ibi & Aganyi, 2015).…”
Section: Review Summarymentioning
confidence: 93%
“…A growing number of empirical studies showed the inverse relationship of external debt and economic growth (Calderon & Fuentes, 2013;Celik & Başkonuş-Direkci, 2013;Cicek, Gozegir, & Cevik, 2010;Cöğürcü & Coban, 2011;Kharusi & Ada, 2018;Muhia & Yasin, 2018;Safdari & Mehrizi, 2011). However, other empirical literature supports the positive association of external debt and growth (Gövdeli, 2019;Musibau, Mahmood, Ismail, Shamsuddin, & Rashid, 2018). Nonetheless, other studies showed no significant association of external debt and sustainable growth (Hassan, Sule, & Abu, 2015;Ibi & Aganyi, 2015;Matthew & Mordecai, 2016).…”
mentioning
confidence: 99%